'Nothing but Nonsense': A Kantian Account of Ugliness. (29th November 2017) - Coate, Matthew
Abstract: What does it mean for something to be judged ugly? On Kant's account of aesthetic judgment, an object judged beautiful brings about a 'free play of the imagination and the understanding', and is thus given as though 'purposive without purpose'; but ugliness, Kant claims, is the 'contrary to beauty'. Assuming Kant is correct on all counts, we would have to conclude that the object judged ugly would bring about a dynamic that is contrary to this ' free play', but that is nevertheless not its mere absence—since its absence is what is exhibited in usual cognitive, non-aesthetic judgment. Likewise, an ugly object is one that would have to be given as though contrapurposive, yet without running counter to any specific end of ours. In this essay, I try to clear up what this can mean, in order to clarify the judgment of ugliness.